Anaplasma phagocytophilum Activates NF-κB Signaling via Redundant Pathways - Dumler, J. Stephen; Lichay, Marguerite; Chen, Wan-Hsin; Rennoll-Bankert, Kristen E.; Park, Jin-ho (Frontiers in Public Health, 2020)
Anaplasma phagocytophilum subverts neutrophil function permitting intracellular survival, propagation and transmission. Sustained pro-inflammatory response, recruitment of new host cells for population expansion, and delayed apoptosis are associated with prolonged nuclear presence of NF-κB. We investigated NF-κB signaling and transcriptional activity with A. phagocytophilum infection using inhibitors of NF-κB signaling pathways, and through silencing of signaling pathway genes. How inhibitors or silencing affected A. phagocytophilum growth, inflammatory response (transcription of the κB-enhanced genes CXCL8 and MMP9), and NF-κB signaling pathway gene expression were tested. Among A. phagocytophilum-infected HL-60 cells, nuclear NF-κB p50, p65, and p52 were detected by immunoblots or iTRAQ proteomics. A. phagocytophilum growth was affected most by the IKKαβ inhibitor wedelolactone (reductions of 96 to 99%) as compared with SC-514 that selectively inhibits IKKβ, illustrating a role for the non-canonical pathway. Wedelolactone inhibited transcription of both CXCL8 (p = 0.001) and MMP9 (p = 0.002) in infected cells. Compared to uninfected THP-1 cells, A. phagocytophilum infection led to >2-fold down regulation of 64 of 92 NF-κB signaling pathway genes, and >2-fold increased expression in only 4. Wedelolactone and SC-514 reversed downregulation in all 64 and 45, respectively, of the genes down-regulated by infection, but decreased expression in 1 gene with SC-514 only. Silencing of 20 NF-κB signal pathway genes increased bacterial growth in 12 (IRAK1, MAP3K1, NFKB1B, MAP3K7, TICAM2, TLR3, TRADD, TRAF3, CHUK, IRAK2, LTBR, and MALT1). Most findings support canonical pathway activation; however, the presence of NFKB2 in infected cell nuclei, selective non-canonical pathway inhibitors that dampen CXCL8 and MMP9 transcription with infection, upregulation of non-canonical pathway target genes CCL13 and CCL19, enhanced bacterial growth with TRAF3 and LTBR silencing provide evidence for non-canonical pathway signaling. Whether this impacts distinct inflammatory processes that underlie disease, and whether and how A. phagocytophilum subverts NF-κB signaling via these pathways, need to be investigated.